C-kit positive cellular network in normal human bowel and in motility disorders - Németh, László (Acta Biologica Szegediensis, 2001)
C-kit positive interstitial cells of Cajal (ICC) appear to have a key role in the normal motility function and development of intestine. They are pacemaker cells, which facilitate active propagation of electrical events and neurotransmission in the bowel wall. The cellular network of ICC is connected by gap junctions to each other and to the smooth muscle cells. Nitrergic innervation is considered to be the most important part of nonadrenergic, noncholinergic innervation in the enteric nervous system. Gut innervation has a complex three-dimensional system that is difficult to appreciate in thin sections. Whole-mount preparation produces a three-dimensional picture to better demonstrate the structure of neuronal networks and their relationship of branching and interconnecting nerve fibres to each other and to the neighbouring tissues. Histochemical and immunohistochemical staining methods combined with whole-mount preparation technique provides a new aspect for studying bowel innervation and distribution of the crucial intracellular molecular architecture. The character-istic profiles of c-kit positive cellular network and nitrergic innervation and their relationship with the smooth muscle fibres in normal gut and in motility disorders provide a morphological basis for investigating intestinal motility disorders.a peripheral nerve injury (N7x) rapidly induces GABAA receptor-dependent disinhibition in the cortex.